Applied mathematics, modeling and computer simulation proceedings of the 4th International Conference (AMMCS 2024), Wuhan, China, 17-18 August 2024 - Chen, Chi-Hua; Wu, Jinsong; Scapellato, Andrea; Berinde, Vasile 1955-; Korzun, Dmitry G.; Zou, Jun (Advances in transdisciplinary engineering, 2024)
Intro -- Title Page -- Preface -- About the Conference -- Contents -- Engineering Applications and Scientific Computations -- A Method for Calculating the Normal Direction Width of Cracks Based on Machine Vision -- Boolean Logic Operations Based on Four-Terminal Magnetic Tunnel Junction for Computing in Memory -- Analysis of the Influence of Blade Tip Reversal Angle on Helicopter Vibration -- Safe Execution of Parallel Component Applications on an Unstable Heterogeneous Cluster Platform -- Optimal Hybrid Reinsurance Strategy Based on the Classic Model of Minimizing Ruin Risk -- Large-Scale Simulated Storage Tank Settlement and Strain Simulation -- Preparation and Application of Crumb Rubber/SBS Composite Modified Asphalt -- Study on Potential Exploitation and Benefit of Flood Control in Waterfall Reservoir -- Simulation of Intelligent Systems -- Study on the Internal Flow Choking of Dual-Thrust Solid Rocket Motors -- Ship Hull Rinsing Water Squirt Pipe Inlet and Outlet Velocity Analysis -- Mulberry Leaf Picking Device Design and Motion Simulation -- Lightweight Design of the Axle Under Different Working Conditions for Carbon Reduction -- Modeling and Application in Vehicle Dynamics Model of Torque Converter Based on Simulink -- Design of Simulation System Based on Real Time Fiber Reflective Memory -- Development of Multi-Objective Spatial Position Testing Technology -- Optimization Design of the Core of Motor Based on Transient Dynamics -- Research and Application of Thermal Power Centralized Control Operation Training System -- Lightweight Design of Special Vehicles Brake Camshaft Considering Torque and Fatigue Life -- Study on the Simulation of Plunger Adaptive Motion and Leakage Velocity Calculation Model in Plunger Gas Lift Wells.